Short Communication: Isolation and identification of actinomycetes potential as the antagonist of Dickeya zeae pineapple soft rot in Lampung, Indonesia - TITIK NUR AENY; JOKO PRASETYO; RADIX SUHARJO; SUSKANDINI R. DIRMAWATI; EFRI EFRI; AININ NISWATI (Biodiversitas Journal of Biological Diversity, 2018)
Aeny TN, Prasetyo J, Suharjo R, Dirmawati SR, Efri, Niswati A. 2018. Isolation and Identification of actinomycetes potential as the antagonist of Dickeya zeae pineapple soft rot in Lampung, Indonesia. Biodiversitas 19: 2052-2058. This study was aimed to collect and identify actinomycetes from the rhizosphere of pineapple with the potency as a biocontrol agent of Dickeya zeae, the pathogen of pineapple soft rot. Soil samples were collected from four different pineapple plantations in Lampung Province, in December 2016. Samples were air-dried, serially diluted, and plated on modified ISP2 medium and several single characterized colonies were sub cultured and purified. The growing colonies were grouped into different colour series based on their aerial-mycelia and substrate-mycelia colors. Antagonistic activity of the actinomycetes isolates were evaluated against Dickeya zeae by agar diffusion method using the same medium agar lawn with the bacterial cultures. Selected antagonistic actinomycete isolates with the biggest clear zone formation were further characterized and identified molecularly based on 16S rDNA sequences. The results showed that as many as 34 actinomycete isolates collected from pineapple rhizosphere produced clear zones. Two isolates, namely GGF2-i5 and GGF4-i18, presented the biggest clear zone were proposed as the potential antagonist strains against D. zeae and identified as Streptomyces parvulus and Streptomyces hygroscopicus subsp. hygroscopicus, respectively. Both of the 16S rRNA gene sequences from those strains were deposited in the GenBank with the accession number MH170279 and MH170280, respectively.